Pengaruh nilai K-value dan Penambahan Filler terhadap Kualitas Kulit Sintetis berbasis Polivinil Klorida - Muh. Wahyu Syabani; Ina Amaliana; Yuniarti Yuniarti (Universitas Jayabaya, 2022)
Synthetic leather is generally made using polyvinyl chloride or polyurethane resins by coating method. The balance between quality and production costs of the final product is influenced by the selection of the right material composition. Polyvinyl chloride resins are available in a variety of k-values, while fillers are often added to modify mechanical characteristics and lower the costs. The aim of this study was to examine the effect of the k-value of polyvinyl chloride blend and the amount of filler on the quality of synthetic leather. Plastisol is prepared by mixing resin, primary plasticizer, secondary plasticizer, and stabilizer according to the formulation. PVC resin blend with different k-values and certain amount of filler (10, 20, 30 and 40 phr) were used. The quality of the samples was tested using adhesion strength, tensile strength, and elongation at break testing according to ASTM D751-06. The results showed that resins blend with different k-values could be used to obtain the desired quality. The value of the adhesion strength, tensile strength and elongation at break will approach the characteristics of the larger part of the resin. The homogeneity of plastisol because of resin blend also needs attention, especially if the k-value difference between two resin is too large. Meanwhile, the use of calcium carbonate as filler in general will reduce the test results obtained.